Using social media to disseminate education about Alzheimer's prevention & treatment: a pilot study on Alzheimer's Universe (www.AlzU.org). (3rd April 2018) - Isaacson, Richard S.; Seifan, Alon; Haddox, Candace L.; Mureb, Monica; Rahman, Aneela; Scheyer, Olivia; Hackett, Katherine; Caesar, Emily; Chen, Jaclyn L.; Isaacson, Jon; McInnis, Mark; Mosconi, Lisa; et al.
ABSTRACT: Background: The use of social media may be a valuable tool for dissemination of patient education interventions. However, in Alzheimer's disease (AD), little data exists about the effectiveness, associated cost, or conditions for utilization. Method: Alzheimer's Universe (www.AlzU.org ) is an online educational portal that provides evidence-based educational content for the public, and a variety of activities related to optimizing AD management. The primary goal of our study was to assess the effectiveness of using the social media platformFacebook.com as a tool to recruit subjects to visit AlzU.org via targeted advertising and evaluate the associated costs. Secondary outcomes included AlzU.org join rates, lesson and activity completion rates, user demographics and attitudes about the education research platform. Results: A total of 706 generated 4268 visits to AlzU.org via a series of page posts promoted with targeted advertising to individuals with previously expressed interest in 'Alzheimer's disease, ' to those who had 'liked' the Alzheimer's Association page, and followers ofwww.facebook.com/AlzheimersDisease . Advertising used different promotional taglines in the Facebook Advertising manager tool using 'Cost Per Click' and the 'Optimized for Engagement' settings. Across all strategies combined, 503 visitors joined AlzU.org (11.8% join rate), 412 engaged with at least one lesson/activity (82%), and 100 completed all available lessons and activities (19.8%). Users were primarily women (79.8%) and the most common age group was 50's (43.3%, range 22–92). The majority joined AlzU.org to learn more about AD prevention or treatment (66.3% and 65.3%, respectively). Over 90% were satisfied with their experience. Discussion: Subjects were quickly and cost-effectively recruited to AlzU.org. Completion rates of education content and activities were adequate, and subjects were highly satisfied with their experiences. Overall, targeted advertising on Facebook.com was an effective means of disseminating AD education online.